2018
DOI: 10.1093/ptj/pzy049
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the Boston University Osteoarthritis Functional Pain Short Form (BU-OA-FPS)

Abstract: The BU-OA-FPS provides reliable and valid measurement of functional pain. Pragmatic studies may consider the BU-OA-FPS for use in electronic health records to capture outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Despite the numerous studies published on the benefits of PT/OT in older adults, few studies have conducted physical and occupational therapies for pain management in CIOAs [34,35]. One study reported that nonpharmacological treatments like mobility/ positioning, nutrition/intake, massage/touch, pacing, therapeutic communication, and spiritual care had no statistically significant difference in pain management in older adults with cognitive impairment in nursing homes (p = 0.296) [38].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…Despite the numerous studies published on the benefits of PT/OT in older adults, few studies have conducted physical and occupational therapies for pain management in CIOAs [34,35]. One study reported that nonpharmacological treatments like mobility/ positioning, nutrition/intake, massage/touch, pacing, therapeutic communication, and spiritual care had no statistically significant difference in pain management in older adults with cognitive impairment in nursing homes (p = 0.296) [38].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%